Development and Validation of a 3-D Printed Tendon-Driven Flexible Continuum Robot - Queiroz, Icaro; Vieira, Miguel; Monteiro, Humberto; Cerqueira, Mateus; Viturino, Caio; Silva, Lucas (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
F1exible continuum robots have been a growing research field in robotics over the last years. The movement of those robots does not happen with joints as in traditional robots, and the understanding of how to actuate a flexible body is critical for modeling and control systems. This work presents a 3D-printed tendon-driven continuum manipulator with 2 coupled sections actuated by servomotors. The robot has been manufactured in polyamide-12 (PA-12), material renowned for its flexibility, endurance, and suitability for flexible robotic applications. During testing, a constant velocity trajectory is executed by each motor with a steady positive and negative speed. This path effectively highlights the manipulator’s capacity for executing complex maneuvers, such as fully contracted “C” and “S” shaped formations. The effort and velocity feedback from motors were collected during the trajectory execution. Results allowed us to obtain a direct relation between this data and the robot’s position, providing valuable information for further implementations.